Jerome J. Pollitt (ed.) The Cambridge History of Painting in the Classical World. - D’Angelo, Tiziana (Journal of Greek Archaeology, 2019)
Reconstructing a single coherent history of painted images over almost two and a half millennia and across a wide variety of cultural contexts in the Mediterranean and Europe is a daunting task, especially today, at a time when the notions of diversity and multiplicity play a crucial role in the study of classical antiquity. The editor Jerome J. Pollitt introduces this study as the first attempt, after Mary Hamilton Swindler’s 1929 Ancient Painting, to provide a comprehensive and up-to-date survey of ancient Greek and Roman panel and mural painting from the Bronze Age to Late Antiquity, and to offer a critical assessment of past and current research on the paintings’ style, technique, iconography and sociocultural context. This ambitious study gathers nine essays by world-leading experts in different areas of ancient painting and is an essential tool for both students and specialists.